ANALISA OPERASI PENGUJIAN KARAKTERISTIK PEMBEBANAN DC SHUNT MOTOR BERBASIS HMI TERHADAP PERUBAHAN PEMBEBANAN GENERATOR DC - Wawolangi, Andino; Kapoh, Syalomita Via Irenly; Ariana, I Wayan Dika; Tuwongkesong, Samsu; Pangemanan, Tjerie (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study reports the design and implementation of an HMI-based monitoring system for the characteristic testing of a DC motor-generator set at the Energy Conversion Laboratory of Politeknik Negeri Manado. The system uses a PZEM-017 DC sensor, Omron CP1E-N30DT PLC (programmed in CX-Programmer), and Omron NB7W-TW01B HMI (designed in NB-Designer), with Modbus RTU RS485 (9600 bps) as the communication protocol. The load consists of six incandescent lamps rated 60 W each, switched individually through solid state relays controlled by the PLC. Testing was conducted under seven conditions: no-load and one to six lamps active. Voltage, current, and power were measured simultaneously by the digital sensor and a reference analog multimeter, while motor speed was recorded with a tachometer. As the load increased from zero to six lamps, the digital voltage dropped from 173 V to 137 V, the digital current rose from 0.63 A to 1.23 A, and the motor speed decreased from 1,992 RPM to 1,709 RPM. The measured speed regulation was 16.56%, while the voltage regulation reached 26.28% (digital) and 25.00% (analog). Verification between calculated power (V × I) and the displayed power on the PZEM-017 produced an average error of only 0.91%, with two of the seven test points showing zero error. The HMI-based monitoring system proved capable of acquiring and displaying motor-generator parameters in real time with accuracy comparable to conventional analog instruments.